Phrarātchabanyat Rabīap Khārātchakān Phonlarư̄an : kǣkhai phœ̄mtœ̄m pen patčhuban tām prakāt Khana Patiwat chabap thī 19-1, Phrarātchabanyat Rabīap Khārātchakān Phonlarư̄an chabap thī 2, chabap thī 3, chabap thī 4 læ chabap thī 5 - Nithiphat Thanasāt; Kawīwut Kānčhanakō̜n; ʻAnan Sawāngsī (Krung Thēp Mahā Nakhō̜n : Samnakphim Phatthanā Sưksā, 1975)
Thai Civil Service Regulations Act, 1992.
Includes bibliographical references.
Keywords: Civil service -- Thailand; Thailand -- Officials and employees